INVENTARISASI DAN POTENSI MANFAAT TUMBUHAN LIAR DI BAWAH TEGAKAN PINUS (PINUS MERKUSSI) DI KABUPATEN GOWA SULAWESI SELATAN - Sudewi, Sri; Saleh, Abdul Rahim (Agriculture Faculty of Flores University, 2025)
Palm oil is one of the plantation commodities that play an important role in the Indonesian economy. Wild plants are still considered as harmful plants because in general people do not know their benefits. The purpose of this study was to identify and document wild plant species that grow under pine stands in Tinggimoncong District, Gowa Regency, South Sulawesi and analyze the potential benefits of wild plant species, especially related to their use in the fields of health, economic agriculture and other value-added products. The method used was the Exploration Method by exploring the research location of the habitat of wild plants under pine stands. The identification process is carried out by taking pictures of samples through the Picture This application available on the Google Playstore platform then matching using an invasive plant identification book. The results of the study found as many as 20 species of potential wildplants consisting of the families Asteraceae Poaceae Phyllanthaceae, Melastomataceae, Umbelliferae, Lamiaceae, Nephrolepidaceae, Polypodiaceae, Urticaceae, Plantaginaceae, Polygalaceae, Pteridaceae, Solanaceae, Rubiaceae, Verbenaceae, Caryophyllaceae. Families from Asteraceae, Poaceae, and Polypodiaceae produced more than 1 wild plant species compared to other families which only produced an average of 1 plant species. Overall, wild plants found under pine stands are useful as medicinal plants. Some species are useful as food for animal feed, ornamental plants, mosquito larvicides, foot sanitizers, sunscreen, natural pesticides, insecticides, and vegetable herbicides. This research contributes to the development of science, providing a positive impact on the empowerment of local communities, which not only provides scientific contributions but also sustainable socio-economic and environmental.